Peran Pembelajaran IPA Dalam Membangun Kompetensi Literasi Sains Siswa Sekolah Dasar - Muhammad Fadlurrahman; I Wayan Suastra; I Made Itra Wibawa; Ida Bagus Putu Arnyan (Jurnal Ilmiah Global Education, 2026)
This study aims to analyze the role of science learning in developing elementary school students’ science literacy competencies, including scientific knowledge, science process skills, and scientific attitudes. The research employed a qualitative descriptive approach with data collection techniques consisting of observation, interviews, and document analysis. Data were analyzed through reduction, presentation, and conclusion drawing. The results indicate that science learning is still dominated by lecture methods, while the use of inquiry, experiments, and active learning models remains limited. Students’ scientific activities are not yet optimal, resulting in uneven development of science process skills such as observing, predicting, and concluding. Teachers face obstacles including limited pedagogical competence and learning facilities, which affect the variety of teaching methods. Overall, students’ science literacy development is at a moderate level, with main weaknesses in understanding abstract concepts and interpreting data. This study emphasizes the importance of activity-based science learning to enhance elementary students’ science literacy